GPS and internet based GIS application for the support of agricultural advisory systems - Szabó, József; Bakos, László; Pásztor, László; Cservenák, Róbert; Pogrányi, Károly (Acta Agraria Kaposváriensis, 2002)
GIS adaptation and digital reambulation of large-scale information on land resources originating from various surveys and sources has become a key issue in Hungary due the recent challenges (like requirements raised by Hungarys EU-accession, introduction of national agri-environmental program, operational practice of precision agriculture etc.). These data are distributed among various organizations and can be found in diverse forms or there are no available data at all. The aim of systematization and harmonization of this information within a uniform GIS is the development of the large scale module of the Hungarian production database for the determination of the optimal functions of agriculture in a given region, together with the harmonization of agricultural production and the protection of land and environment. Agricultural advisory and recommendation systems summarize current knowledge on soil fertility, nutrient supply and limiting factors with respect to the expected yield. A potential step in the improvement of these advisory and recommendation systems could also be the extension of their spatial features that is integrating them with GIS. A complex GI system was elaborated by the GIS Laboratoty of RISSAC in close co-operation with the Plant and Soil Conservation Service of Fejér Country for the whole territory (about 3,500 ha) of a co-operative farm in Central Hungary. In addition to cany ing out the digital reambulation and GIS adaptation of large-scale soil mappings further information was integrated into the system: (1) topographic data, ensuring the delineation of the geographical environment and helping information processing and positioning; including a DEM; (2) property register data determining the ownership and registration conditions of parcels; (3) multitemporal data of nutrient control based fertilization advisory system monitored yearly. As a next step an Intranet/Internet based realization of the system was worked out using Autodesk MapGuide Program. This type of user interface can be learnt and used by anyone and could provide fast access to the spatial data and is operating system independent. Internet also provides other useful advantages since Internet browsers are available almost everywhere and this technology provides access to the server for unlimited number of users. The GIS server can also be reached from mobil clients, which (supplied with suitable GPS-cards) make GIS supported, real-time, in-situ survey possible. The elaborated system can prove to be very usefid in the practice of field work of agricultural counselling.